Framing Research and Assessment of Co‐Curricular Learning. Issue 164 (December 2015) - Meents‐DeCaigny, Ellen; Sanders, Liz
Abstract : The purpose of this chapter is to provide an overview of important theories and frameworks that ground research and assessment of co‐curricular learning.